Advances in trabecular meshwork stem cells transplantation for primary open angle glaucoma - Xin Jiang (Guoji Yanke Zazhi, 2019)
Primary open angle glaucoma is a kind of chronic disease characterized by progressive damage to the optic disc as a result of persistent elevation of intraocular pressure. The complicated and unidentified mechanism of primary open angle glaucoma makes its clinical treatment relatively difficult nowadays. In primary open angle glaucoma, IOP elevation is often a result of reduced aqueous humor flow through the trabecular meshwork, which plays an important regulating role in drainage process. The morphology, quantity, structure and function of trabecular meshwork cell can increase the outflow resistance of aqueous humor, leading to elevation of IOP. Research is proving that induced pluripotent stem cells(iPSCs), bone mesenchymal stem cells(BMSCs)and adipose-derived stem cells(ADSCs)have been used for trabecular meshwork cell differentiation and regeneration, providing a reliable cell source for trabecular meshwork stem cell replacement therapy in primary open angle glaucoma. Recent studies have showed that trabecular meshwork stem cells have absolute superiority in differentiating into trabecular meshwork cells, which provides new target for cell transplantation to treat glaucoma. This marks a new era of stem cell therapy for primary open angle glaucoma and also brings new hope to the treatment of glaucoma. This article reviews different types of stem cells for trabecular meshwork transplantation and may provide novel development of therapeutic strategies for primary open angle glaucoma with cell transplantation in the future.